Pengembangan Aplikasi Pengenalan Pahlawan Revolusi Indonesia Berbasis Android - Ekowati, Maria Atik Sunarti; Dananti , Kristyana; Wening, Sri (Universitas Boyolali, 2024)
The development of Android applications is currently growing rapidly, which is the background for this research, there are various free and paid Android applications available on Google Play that we can install on Android-based smartphones according to our needs. The increasing development of Android applications nowadays opens up very promising opportunities for anyone who wants to become an Android application developer. The aim of this research is to make it easier for the public to get to know the heroes of the Indonesian Revolution, as well as to attract user interest who want to know and learn about the Heroes of the Indonesian Revolution and at the same time remind the public about the struggles carried out by the Heroes of the Indonesian Revolution. The method used in the research is the research & development method (R&D Method). The R & D method is a research method used to produce certain products and test the effectiveness of these products. The result of the research is the development of an Android-based application for recognizing the heroes of the Indonesian Revolution.